In vitro models for head and neck cancer: Current status and future perspective - Moya-Garcia, Christian R.; Okuyama, Hideaki; Sadeghi, Nader; Li, Jianyu; Tabrizian, Maryam; Li-Jessen, Nicole Y. K. (Frontiers in Oncology, 2022)
The five-year overall survival rate remains about 50% for head and neck cancer patients even though new cancer drugs have been approved for clinical use since 2016. Cancer drug studies are now moving towards the use of 3D culture models for better emulating the unique tumor microenvironment and better predicting in vivo response to cancer treatments. Distinctive tumor microenvironment features, such as tumor geometry, heterogenous cellularity, and hypoxic cues, notably affect tissue aggressiveness and drug resistance. However, these features have not been fully incorporated into in vitro head and neck cancer models. This review paper aims to provide a scholarly assessment of the designs, contributions, and limitations of in vitro models in head and neck cancer drug research. We first review tumor microenvironment features of head and neck cancer that are most relevant to in vitro drug evaluation. We then evaluate a selection of advanced culture models, namely spheroids, organotypic models and microfluidic chips, in their applications for head and neck cancer drug research. Lastly, we propose future opportunities of in vitro head and neck cancer research in the prospects of high-throughput drug screening and patient-specific drug evaluation.